y=-3x^{2}-18x-25 x1 = 2
Calculamos y1 sustituyendo x1 en la ecuación:
y1 = -73
Esta es también la ordenada del simétrico:
ys = -73
xs = x1 - 2·(x1 - x_eje) = -b/a - x1
xs = -8
| y=2x^{2}+8x+7 x1 = -1
y1 = ...
ys = ...
xs = ...
| y=-x^{2}+4x-4 x1 = 2
y1 = ...
ys = ...
xs = ...
|
y=3x^{2}-12x+12 x1 = -4
y1 = ...
ys = ...
xs = ...
| y=3x^{2}-6x+2 x1 = 0
y1 = ...
ys = ...
xs = ...
| y=-2x^{2}+8x-7 x1 = 1
y1 = ...
ys = ...
xs = ...
|
y=2x^{2}+4x x1 = -2
y1 = ...
ys = ...
xs = ...
| y=2x^{2}-8x+7 x1 = 5
y1 = ...
ys = ...
xs = ...
| y=x^{2}+6x+11 x1 = 0
y1 = ...
ys = ...
xs = ...
|
y=-x^{2}-2x-1 x1 = 3
y1 = ...
ys = ...
xs = ...
| y=-2x^{2}-1 x1 = -5
y1 = ...
ys = ...
xs = ...
| y=x^{2}-2x+2 x1 = 2
y1 = ...
ys = ...
xs = ...
|
y=3x^{2}+18x+27 x1 = 5
y1 = ...
ys = ...
xs = ...
| y=3x^{2}-2 x1 = 5
y1 = ...
ys = ...
xs = ...
| y=x^{2}+6x+9 x1 = -4
y1 = ...
ys = ...
xs = ...
|
y=-x^{2}-2x+1 x1 = 3
y1 = ...
ys = ...
xs = ...
| y=2x^{2}+4x+2 x1 = 3
y1 = ...
ys = ...
xs = ...
| y=2x^{2}-12x+20 x1 = -1
y1 = ...
ys = ...
xs = ...
|
y=-x^{2}-4x-3 x1 = 3
y1 = ...
ys = ...
xs = ...
| y=x^{2} x1 = -2
y1 = ...
ys = ...
xs = ...
| y=3x^{2}-6x+3 x1 = 0
y1 = ...
ys = ...
xs = ...
|
y=-x^{2}+2x-3 x1 = -5
y1 = ...
ys = ...
xs = ...
| y=x^{2}-2x+2 x1 = 4
y1 = ...
ys = ...
xs = ...
| y=x^{2}-1 x1 = -4
y1 = ...
ys = ...
xs = ...
|